A captura do movimento do discurso e a produção de sentidos: as entrevistas como dispositivo de análise na clínica fonoaudiológica - Givigi, Rosana Carla do Nascimento (2009)
This article is part of a research project developed at the speech therapy program in the Federal University of Sergipe. It analyses how the significations and senses attached to subjects with significant language disorders are constituted and kept. In order to do so, discourses about these subjects by family members are used. Language will be considered as a product of the articulation between social organization and psychic singularity. The article also discusses the discourse in its social dimension and its echo with other enunciations. Since it is oriented by conversations with historical-cultural principles and by the thoughts of Bakhtin, this study emphasizes the active role of the other, always in a bilateral process, through a device called dialogism. The article rescues the paths taken towards the formation of a group of parents in the speech therapy clinic and analyses the initial interviews as a way of selecting these parents. It considers that discourse, along with actions, change meanings and build new scenarios.